Electronic Customer Relationship Management and Competitive Performance of Money Deposit Banks in Nigeria: Theoretical Review (Singaporean Journal of Business Economics and Management, 2018)
In recent time, integration of Information communication Technology has changed the ways in which businesses are being carried out. This has moved the focus of traditional customer relationship management to electronic customer relationship manage. The problem envisaged that led to this study hinges on the fact that there is abundant of literature from developed countries around the global on how firms use E-CRM to improve its performance. But in Nigeria, there is paucity in theoretical literature on the effect of E-CRM on competitive performance of money deposit banks in Nigeria. The objective of this study is to explore theoretically the effect of electronic customer relationship management on competitive performance of money deposit banks in Abia State. A conceptual framework was critical dealt with, theory of competitive advantage and commitment-trust theory was review and theory of competitive advantage was adopted as the theoretical underpin for the study. Various empirical studies were reviewed. The study found out that The core technologies of E-CRM is network and ICT facilities, e-CRM is a system that runs 24/7 hours, E-CRM is impersonal in operation, developing a strong customer relationship using E-CRM is considered a competitive strategy, e-CRM enables banks to provide personalized services to different group of customers and so on. The study concluded that effective and efficient E-CRM is very vital for any bank to attain competitive advantage it the competitive marketing environment. It was recommended that Since the core technologies of E-CRM is network and ICT facilities, banks should provide an efficient network and ICT facilities sufficient for the operation of E-CRM and so on. Limitations of the study/suggestion for further studies were given.